Association between life’s essential 8 and testosterone deficiency in US men: findings from national health and nutrition examination survey (NHANES) 2011–2016 - Mei, Yangyang; Ji, Nuo; Zhang, Bo; Xia, Wei; Feng, Xingliang; Xu, Renfang; Xue, Dong (Frontiers in Endocrinology, 2024)
Background: Testosterone deficiency (TD) is closely associated with cardiovascular diseases (CVD). We intended to explore the association of Life's Essential 8 (LE8), the recently updated measurement of cardiovascular health, with the prevalence of TD among US male adults.The population-based cross-sectional study selected male adults aged 20 years or older from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016. According to the American Heart Association definitions, the LE8 score was measured on a scale of 0-100, and divided into health behavior and health factor scores, simultaneously. Furthermore, these scores were categorized into low (0-49), moderate (50-79), and high (80-100) classifications. TD is defined as a total testosterone level below 300ng/dL. Correlations were investigated by weighted multivariable logistic regression, and the robustness of the results were verified by subgroup analysis.Results: A total of 4971 male adults with an average age of 47.46±0.41 years were eligible for the final analyses, of whom 1372 were determined to have TD. The weighted mean LE8 score of the study population was 68.11±0.41. After fully adjusting potential confounders, higher LE8 scores were significantly associated with low risk of TD (odd ratio [OR] for each 10-point increase, 0.79; 95% CI, 0.71-0.88) in a linear dose-response 4 relationship. Similar patterns were also identified in the association of health factor scores with TD (OR for each 10-point increase, 0.74; 95% CI, 0.66-0.83). These results persisted when LE8 and health factor scores was categorized into low, moderate, and high groups. The inversed association of LE8 classifications and TD remained statistically significant among older, obese, and men without CVD.Conclusions: LE8 and its health factor subscales scores were negatively associated with the presence of TD in linear fashions. Promoting adherence to optimal cardiovascular health levels may be advantageous to alleviate the burden of TD.